Rancang Bangun Sistem Informasi Pembiayaan Kredit Mobil Pada PT Mandiri Tunas Finace Pontianak - Arizona, Nanda Diaz; Yulia, Yulia; Adiansyah, Adiansyah (Building of Informatics, Technology and Science (BITS), 2021)
PT. Mandiri Tunas Finance is a car showroom company that serves car sales on credit, which is located on Jl. Ayani Megamall Complex Block B. No. 35 36.PT. Mandiri Tunas Finance is a company as an intermediary or service that helps or cooperates with partners in the car loan process. The partner is a limited liability company that sells car units on credit, but if the prospective buyer wants a car loan, the partner will obtain data on the prospective customer's credit application which will then be processed through Mandiri Tunas Finance. Therefore, there are still many partners who need a place to disseminate information on car units with the credit method so that they are widely known by external parties and make it easier for the car loan financing process. So the author makes a website-based car loan financing application at PT. Mandiri Tunas Finance uses the PHP (Hypertext Processor) programming language, where this application is made for prospective customers to be able to access the website to apply for a car loan easily and simply select the desired car unit on the website